PENGARUH PERHATIAN ORANG TUA DAN DISIPLIN BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS KELAS VIII SMP NEGERI 12 PEMATANGSIANTAR - Hans Yohanes Maxwell Pasaribu; Anton Luvi Siahaan; Paulina Herlina Sirait (JOURNAL SAINS STUDENT RESEARCH, 2024)
This study aims to gain knowledge about the effect of parental attention and learning discipline on learning outcomes in social studies class VIII SMP Negeri 12 Pematangsiantar.This research is quantitative in nature with the testing media used is SPSS 22. The population in this study were all students in grade VIII of SMP Negeri 12 Pematangsiantar. The sampling technique used Simple Random Sampling as many as 72 respondents. The data collection technique used was a questionnaire. Instrument tests use normality tests and reliability tests. Data analysis techniques use classical assumption tests, namely normality test, multicollinearity test, heteroscedasticity test, and hypothesis testing, namely multiple linear regression analysis, t test, f test, and coefficient of determination.The research data and data management of the partial test (t-test) show that the variable X₁ obtained -5.383 < the value of 1.66691 so it can be concluded that parental attention has a negative and significant effect on student learning outcomes. Variable X₂ obtained t count 3,177> value 1.66691 so it can be concluded that learning discipline has a positive and significant effect on student learning outcomes. Simultaneous test data management (f test) obtained that 14,689> 2.38 .